Characterization of Matrix Metalloproteinases (MMPs) and CTCF protein expressions in several human cancer cell lines in vitro - Mat Alewi, Nur Aizura; Abdull Rasad, Mohammad Syaiful Bahari (2013)
Collagenases are proteins from the matrix metalloproteinases (MMPs) family which are comprised of secreted and membrane-bound endopeptidases that play a crucial role in tumor invasion. Previous studies have suggested that collagenases, such as Collagenase 1 (MMP-1) and collagenase 3 (MMP-13), may have a significant influence in the expression of CTCF proteins, which have also been implicated in numerous cancer studies. However, the depth of involvement of these proteins in the fundamental molecular mechanisms of cancer remains to be poorly known. This study aims to determine the degree of MMP-1, MMP-13 and CTCF protein expressions in several human cancer cell lines and to ascertain its probable involvement in cancer development. The qualitative expressions of the proteins in skin melanoma (A375), breast cancer (MCF-7) and cervix cancer (HeLa) cells were demonstrated through Western Blot analysis. Analysis of the results showed that the strongest expression for MMP-1 was detected in HeLa cells, while MCF-7 and A375 cells produced very weak/non-detectable protein expressions. In contrast, both MMP-13 and CTCF proteins were highly expressed at varying degree of expressions in all three cells, with HeLa cells producing the strongest protein expressions. Overall, the results depict a prominent presence and the probable involvement of MMP-1, MMP-13 and CTCF proteins in the development and metastasis of cancer. Thus, it is believed that obtaining a detailed understanding of MMPs and it interacting partners may be vital for future endeavors in respect to the possible design of therapeutic MMP strategies for prospective medical applications.